Hyperplastic Polyp? Look Again... The Impact of the New Classification for Serrated Polyps - Fidalgo, Catarina (2014)
Introduction: The World Health Organization reviewed the classification for serrated colonic polyps in 2010. A new entity, sessile serrated adenoma, was included with two variants: with and without cytological dysplasia. This lesion’s malignant potential has been recognized and according to the new classification, many polyps may be reclassified. The impact of this change is yet to be assessed.Objective: Analyze the proportion of lesions that were reclassified according to the new World Health Organization classification and the variables that influenced it.Material and Methods: Every patient with at least one sessile serrated adenoma diagnosed in a 5 year period was included. All polyps (regardless of type) resected during the study period were reviewed. Data concerning polyp’s characteristics and patient variables were collected. Forty consecutive patients were included [13 female, mean age at 1st sessile serrated adenoma -59 yrs (34-80)].Results: Were reviewed 247 polyps: hyperplastic - 42%; conventional adenomas - 29%; sessile serrated adenoma - 24%; serrated adenomas - 5%. Sixty-three polyps were reclassified: 43 hyperplastic, 12 serrated adenomas, 7 sessile serrated adenoma and 1 conventional adenoma with low grade dysplasia. Reclassification was significantly greater for hyperplastic polyps when compared with the other subtypes. Forty-three of one hundred and four (41%) hyperplastic polyps were reclassified all as sessile serrated adenoma. In these polyps the probability of reclassification was independent from polyp location but was greater if polyp size ≥ 5 mm.Discussion: This is a single center, rectrospective study. The fact that it was done in an Oncology Referral Institution with a Family Risk Clinic may have influenced the results. Nevertheless the impressive reclassification rate for Hyperplastic Polyps and the fact that they were reclassified mainly as Serrated Adenomas makes these results relevant to daily practice.Conclusion: Our results suggest that, according to the new World Health Organization classification for serrated colonic polyps, a considerable proportion of hyperplastic polyps will be reclassified. The serrated pathway of colorectal carcinogenesis has probably been underestimated and at-risk patients may have been under inappropriate surveillance.Keywords: Colonic Neoplasms/diagnosis; Colonic Polyps/classification; World Health Organization; Neoplasm Grading.